Cyclic behaviour of Johor sand - Marto, Aminaton (GEOMATE International Society, 2016)
Series of laboratory testing on the investigation of soil liquefaction using cyclic triaxial test had been carried out by researchers around the world but many of the results are contradictory. Thus, it is important to first determine the condition in which the clean sand is most susceptible to liquefaction, then only the liquefaction susceptibility of sand matrix soils could be compared and discussed under this specific condition. This paper presents the undrained behaviour of Johor sand and sand mixed with fines (kaolin) from cyclic triaxial tests. Stress controlled triaxial test apparatus was used to shear the isotropically consolidated soil samples under undrained two-way cyclic loading until the initiation of liquefaction. The liquefaction was defined based on: (i) excess pore pressure was equal to effective confining pressure or (ii) double amplitude strain of 5 % was reached, whichever was achieved first. The results of two-way cyclic triaxial tests on clean sand showed that besides the cyclic stress ratio, the liquefaction resistance of the sand under undrained loading was proportional to effective consolidation pressure and density index. The Johor sand was more liquefiable at its loose state and under low effective consolidation pressure, when subjected to earthquake loading.